Effect of Capital Structure on ESG Performance in ASEAN Islamic Banking: Environmental, Social, and Governance Perspectives - Amellia Zahro; Esy Nur Aisyah (Electronic Journal of Education, Social Economics and Technology, 2025)
ESG performance shows how the company carries out its commitment to environmental, social and good governance aspects. In the banking industry, including Islamic banks, the implementation of ESG can improve the image and trust of customers. This study analyzes the effect of capital structure-including Total Shareholder Equity to Total Asset (SER), Short Term Debt to Asset (STDA), Long Term Debt to Asset (LTDA), and Total Debt to Asset (TDA)-on ESG performance of Islamic banks in ASEAN during 2019-2023. The method used is quantitative with a descriptive approach. Secondary data were obtained from the financial statements of Islamic banks published regularly through the official websites of banks in ASEAN countries such as Indonesia, Malaysia, the Philippines, and Singapore. The research sample consisted of 33 Islamic banks, with 20 banks selected using purposive sampling technique. The analysis tool employed is panel regression analysis using EViews 13 software. The results showed that capital structure (SER, STDA, LTDA, and TDA) simultaneously has a positive and significant effect on the ESG performance of Islamic banks in ASEAN. This finding indicates that Islamic banks maximize the use of external funds for business expansion and increase profitability.